2021
DOI: 10.1038/s43247-021-00231-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation arrested the mainshock rupture of the 2016 Central Tottori earthquake

Abstract: After a large earthquake, many small earthquakes, called aftershocks, ensue. Additional large earthquakes typically do not occur, despite the fact that the large static stress near the edges of the fault is expected to trigger further large earthquakes at these locations. Here we analyse ~10,000 highly accurate focal mechanism solutions of aftershocks of the 2016 Mw 6.2 Central Tottori earthquake in Japan. We determine the location of the horizontal edges of the mainshock fault relative to the aftershock hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Japan is located in the plate subduction zone, where numerous earthquakes have occurred, and much data has been obtained on these earthquakes. Earthquakes occurred in Japan with unknown relationships to active faults include the 1984 Western Nagano Earthquake (Mj 6.8), the 1997 Northern Yamaguchi Earthquake (Mj 6.6), the 1997 Northwestern Kagoshima Earthquake (Mj 6.6, 6.4), the 2000 Western Tottori Earthquake (Mj 7.3), and the 2016 Central Tottori Earthquake (Mj 6.6) (K. Kato et al, 2004;Toda, 2013Toda, , 2016Iio et al, 2021). K. Kato et al (2004) showed that a total of 10 inland earthquakes with magnitudes of Mj 6 or greater that occurred between 1953 and 2004 in Japan; among them, there were four cases where the active fault was not known in advance.…”
Section: Introductionmentioning
confidence: 99%
“…Japan is located in the plate subduction zone, where numerous earthquakes have occurred, and much data has been obtained on these earthquakes. Earthquakes occurred in Japan with unknown relationships to active faults include the 1984 Western Nagano Earthquake (Mj 6.8), the 1997 Northern Yamaguchi Earthquake (Mj 6.6), the 1997 Northwestern Kagoshima Earthquake (Mj 6.6, 6.4), the 2000 Western Tottori Earthquake (Mj 7.3), and the 2016 Central Tottori Earthquake (Mj 6.6) (K. Kato et al, 2004;Toda, 2013Toda, , 2016Iio et al, 2021). K. Kato et al (2004) showed that a total of 10 inland earthquakes with magnitudes of Mj 6 or greater that occurred between 1953 and 2004 in Japan; among them, there were four cases where the active fault was not known in advance.…”
Section: Introductionmentioning
confidence: 99%